Clinical, genetic, and functional characterization of the glycine receptor β-subunit A455P variant in a family affected by hyperekplexia syndrome - Aboheimed, Ghada I.; AlRasheed, Maha M.; Almudimeegh, Sultan; Peña-Guerra, Karla A.; Cardona-Londoño, Kelly J.; Salih, Mustafa A.; Seidahmed, Mohammed Z.; Al-Mohanna, Futwan; Colak, Dilek; Harvey, Kirsten; Arold, Stefan T.; Kaya, Namik; et al. (The Journal of biological chemistry, 2022)
Hyperekplexia is a rare neurological disorder characterized by exaggerated startle responses affecting newborns with the hallmark characteristics of hypertonia, apnea, and noise or touch-induced nonepileptic seizures. The genetic causes of the disease can vary, and several associated genes and mutations have been reported to affect glycine receptors (GlyRs); however, the mechanistic links between GlyRs and hyperekplexia are not yet understood. Here, we describe a patient with hyperekplexia from a consanguineous family. Extensive genetic screening using exome sequencing coupled with autozygome analysis and iterative filtering supplemented by in silico prediction identified that the patient carries the homozygous missense mutation A455P in GLRB, which encodes the GlyR β-subunit. To unravel the physiological and molecular effects of A455P on GlyRs, we used electrophysiology in a heterologous system as well as immunocytochemistry, confocal microscopy, and cellular biochemistry. We found a reduction in glycine-evoked currents in N2A cells expressing the mutation compared to WT cells. Western blot analysis also revealed a reduced amount of GlyR β protein both in cell lysates and isolated membrane fractions. In line with the above observations, coimmunoprecipitation assays suggested that the GlyR α1-subunit retained coassembly with βA455P to form membrane-bound heteromeric receptors. Finally, structural modeling showed that the A455P mutation affected the interaction between the GlyR β-subunit transmembrane domain 4 and the other helices of the subunit. Taken together, our study identifies and validates a novel loss-of-function mutation in GlyRs whose pathogenicity is likely to cause hyperekplexia in affected individuals.